Internet Start-Ups – which Influence do the Alma Mater and the University Region have on the Location Decision of Founders? - Kopper, Johannes; Jäger, Angelika (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The regional orientation of academic activities and economic support of the university region are increasingly important responsibilities. The paper examines to which extent academic founders of the online sector decide to establish firms close to their alma mater, and which factors affecting this decision are associated with the university or the region. Are entrepreneurs’ decisions to stay or leave the region dependent upon factors of the region itself? What influence do the structure and strategic focus of the university have on this decision? These questions are of interest for political decision makers and university stakeholders – especially as the regional effectiveness of start-ups and their contribution to regional economy is put into question. This regional effectiveness justifies high public financial support. The analysis is based on the German digital platform Gründerszene, which provides services for founders in the online sector. By using regression analysis, the factors of influence of academic institutions and the region on the location decision of online founders are identified. There is no noticeably higher rate of founders deciding to stay within regions which are strong with knowledge, innovation, and service compared to structurally weak regions. On the other hand, a regional entrepreneurial climate that is conducive for start-ups is very important.
Keywords: Start-up; Regional knowledge transfer; Online sector